2012
DOI: 10.1097/eja.0b013e3283543e43
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in information transfer between anaesthesiologist and postanaesthesia care unit staff

Abstract: This study demonstrates that the handover process is inconsistent and in some cases information defined as important by the physicians and the nurses is not transferred. Further studies need to investigate whether a handover protocol leads to a minimisation of omissions in information transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 21 publications
2
47
0
Order By: Relevance
“…Several studies have reported handovers after surgery in the postanaesthesia care unit (PACU) as being unstructured with omissions of important information about the patient (Anwari, 2002;Milby, Bohmer, Gerbershagen, Joppich, & Wappler, 2014;Nagpal, Arora, et al, 2010;Siddiqui et al, 2012;Smith, Pope, Goodwin, & Mort, 2008). Standardisation of the patient handover process through implementation of checklists and protocols has had a positive influence on the completeness of verbal reporting and practical tasks performed (Agarwal et al, 2012;Nagpal et al, 2013;Petrovic et al, 2015;Weinger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported handovers after surgery in the postanaesthesia care unit (PACU) as being unstructured with omissions of important information about the patient (Anwari, 2002;Milby, Bohmer, Gerbershagen, Joppich, & Wappler, 2014;Nagpal, Arora, et al, 2010;Siddiqui et al, 2012;Smith, Pope, Goodwin, & Mort, 2008). Standardisation of the patient handover process through implementation of checklists and protocols has had a positive influence on the completeness of verbal reporting and practical tasks performed (Agarwal et al, 2012;Nagpal et al, 2013;Petrovic et al, 2015;Weinger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Inefficiencies of communication at clinical handover have been associated with irrelevant, missing or repetitive information, which can result in health professionals spending extensive periods attempting to retrieve relevant and correct information ). In addition, ineffective handovers can cause major problems relating to lack of delivery of appropriate care and the possibility of misuse or poor utilisation of resources (Arora et al 2005, Siddiqui et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Inefficiencies of communication at clinical handover have been associated with irrelevant, missing or repetitive information, which can result in health professionals spending extensive periods attempting to retrieve relevant and correct information . In addition, ineffective handovers can cause major problems relating to lack of delivery of appropriate care and the possibility of misuse or poor utilisation of resources (Arora et al 2005, Siddiqui et al 2012). Previous survey studies of clinical handover have mainly focused on considering the perspectives of doctors (Fassett et al 2007, Karnwal et al 2008, Johner et al 2013, Lindsay et al 2013, Mazhar et al 2013, Kessler et al 2014 or nurses (O'Connell et al 2008, Street et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…While there is no research in the published literature that specifically addresses doctor-nurse communication in the postoperative care of patients who have undergone MFTT, there are a small number of reports in the anesthesiology literature that have analyzed handoffs of patients from the intraoperative anesthesiology team to the recovery room nursing team. [7][8][9] Nagpal et al developed a Postoperative Hand-over Assessment Tool (PoHAT) that reliably identifies deficiencies in the current methods of postoperative handover, such as inadequate communication of anticipated postoperative problems and contingency plans if those problems were to arise. 4 Furthermore, Manser et al developed a comprehensive rating tool to assess the quality of handovers.…”
Section: Discussionmentioning
confidence: 99%